Narkotika dalam Perspektif Fiqh Kontemporer: Analisis Qawā‘Id Fiqhiyyah dan Perbandingan Pendapat Ulama Mazhab - Fattah Hanafi; Aripin Marpaung; Nia Ramadhani; Najma Khairunnisa Nasution; Muhammad Alwi; M. Pryansah; Balkis Alisa Gita; Siti Aisyah; Muhammad Adrian Shahputra; Juan Prasatia; Muhammad Alfarisi; Alif Hadhari Fahzilah; Annisa Tuljannah Br Sagala; Van Dwi Pamungkas; Muhammad Hayqal Bani Hakim Tanjung; Habibullah Abdurrahman T. Bolon; Yudi Maulana Siagian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study discusses narcotics from the perspective of contemporary fiqh with a focus on the analysis of qawā‘id fiqhiyyah and the comparison of opinions among Islamic legal schools (madhhab). Narcotics abuse in the modern era is not only a matter of positive law and public health, but also raises moral, social, and religious problems that require a comprehensive Islamic legal approach. This research aims to analyze the legal basis of narcotics in Islam through the approach of qawā‘id fiqhiyyah, examine the views of the four major madhhab scholars regarding narcotics, and explain their relevance to positive law and contemporary medical developments. This research employs a normative Islamic legal research method with a descriptive-analytical qualitative approach. The data were collected through library research using primary sources such as the Qur’an, Hadith, classical Islamic jurisprudence books, contemporary scholars’ works, and national legal regulations. Data analysis was conducted using content analysis and comparative approaches to compare the perspectives of the Hanafi, Maliki, Shafi‘i, and Hanbali schools regarding narcotics. The results of the study indicate that the majority of Islamic scholars agree that narcotics abuse is prohibited (haram) because it shares the same ‘illat (legal cause) as khamr, namely intoxicating effects, damage to reason, and harmful consequences. The legal determination is strengthened through the application of qawā‘id fiqhiyyah such as al-ḍarar yuzāl (harm must be eliminated), dar’ al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ (preventing harm takes precedence over obtaining benefit), and al-ḍarūrāt tubīḥ al-maḥẓūrāt (necessity permits prohibited matters). This study also finds that Islamic law provides limited permissibility for the medical use of narcotics in emergency situations under professional supervision. Furthermore, a rehabilitative approach toward narcotics addicts is considered more aligned with the principles of maqāṣid al-syarī‘ah than a purely punitive approach. Therefore, contemporary fiqh has strong relevance in addressing modern narcotics issues through a flexible, contextual, and benefit-oriented approach.